Allium Extract Implements Weaned Piglet's Productive Parameters by Modulating Distal Gut Microbiota - Miguel Rabelo-Ruiz; Claudia Teso-Pérez; Juan Manuel Peralta-Sánchez; Juan José Ariza; Antonio Manuel Martín-Platero; Óscar Casabuena-Rincón; Patricia Vázquez-Chas; Enrique Guillamón; María Arántzazu Aguinaga-Casañas; Mercedes Maqueda; Eva Valdivia; Alberto Baños; et al. (MDPI AG, 2021)
Antimicrobial resistance (AMR) has risen as a global threat for human health. One of the leading factors for this emergence has been the massive use of antibiotics growth-promoter (AGPs) in livestock, enhancing the spread of AMR among human pathogenic bacteria. Thus, several alternatives such as probiotics, prebiotics, or phytobiotics have been proposed for using in animal feeding to maintain or improve productive levels while diminishing the negative effects of AGPs. Reducing the use of antibiotics is a key aspect in the pig rearing for production reasons, as well as for the production of high-quality pork, acceptable to consumers. Here we analyze the potential use of Allium extract as an alternative. In this study, weaned piglets were fed with Allium extract supplementation and compared with control and antibiotic (colistin and zinc oxide) treated piglets. The effects of Allium extract were tested by analyzing the gut microbiome and measuring different productive parameters. Alpha diversity indices decreased significantly in Allium extract group in caecum and colon. Regarding beta diversity, significant differences between treatments appeared only in caecum and colon. Allium extract and antibiotic piglets showed better values of body weight (BW), average daily weight gain (ADG), and feed conversion ratio (FCR) than control group. These results indicate that productive parameters can be implemented by modifying the gut microbiota through phytobiotics such as Allium extract, which will drive to drop the use of antibiotics in piglet diet.